Knockouts of Kekkon1 define sequence elements essential for Drosophila epidermal growth factor receptor inhibition. - Alvarado, D.; Rice, A.H.; Duffy, J.B. (Genetics, 2004)
Throughout development, cells utilize feedback inhibition of receptor tyrosine kinase (RTK) signaling as an important means to direct cellular fates. In Drosophila, epidermal growth factor receptor (EGFR) activity is tightly regulated by a complex array of autoregulatory loops, involving an assortment of inhibitory proteins. One inhibitor, the transmembrane protein Kekkon1 (Kek1) functions during oogenesis in a negative feedback loop to directly attenuate EGFR activity. Kek1 contains both leucine-rich repeats (LRRs) and an immunoglobulin (Ig) domain, two of the most prevalent motifs found within metazoan genomes. Here we demonstrate that Kek1 inhibits EGFR activity during eye development and use this role to identify kek1 loss-of-function mutations that implicate the LRRs in directing receptor inhibition. Using a GMR-GAL4, UAS kek1-GFP misexpression phenotype we isolated missense mutations in the kek1 transgene affecting its ability to inhibit EGFR signaling. Genetic, molecular, and biochemical characterization of these alleles indicated that they represent two functionally distinct classes. Class I alleles directly diminish Kek1's affinity for EGFR, while class II alleles disrupt Kek1's subcellular localization, thereby indirectly affecting its ability to associate with and inhibit the receptor. All class I alleles map to the first and second LRRs of Kek1, suggesting a primary role for these two repeats in specifying association with and inhibition of EGFR. Last, our analysis implicates glycine 160 of the second LRR in regulating EGFR binding.